Solving AdS3 string theory at minimal tension: tree-level correlators - Andrea Dei; Bob Knighton; Kiarash Naderi (Journal of High Energy Physics)
Abstract We revisit the minimal tension (k = 1) string theory on AdS3 × S3 × 𝕋4. We propose a new free-field description of the worldsheet theory and show how localization of string amplitudes emerges from the path integral. We exemplify our proposal by reproducing the worldsheet partition function of the psu $$ \mathfrak{psu} $$ (1, 1|2)1 WZW model and providing explicit expressions for spectrally-flowed vertex operators and DDF operators. We compute string correlators in the path integral formalism and obtain a precise tree-level match with correlation functions of the boundary symmetric orbifold.